Estado de exceção em Giorgio Agamben - Pontel, Evandro (2014)
This study investigates the notion of state of exception in Giorgio Agamben as an apparatus that captures the life of the citizen through its own suspension, an empty space of law, a zone of anomie in which all legal determinations come into a zone of indistinctness. The theorization of this legal institute is developed in a perspective of an genealogical and paradigmatic approach in order to situate it on the threshold of the contemporary world and its political consequences and what may mean to act politically today. In order to analyze modern theories of state, the italian thinker employs an artifice of Roman law: the iustitium the suspension, stoppage of law , that produced a legal vacuum. In the Modernity, the state of exception operates continuously with multidimensional forms in which the concentration field is the modern paradigm of the nomos an the bare life reaches its maximum indeterminacy . In the state of exception which unites norm and life, that applies disapplying itself, produces an anomie zone, the challenge is to paralyze the biopolitical machine of the state of exception which determines life on multiple levels, since the earliest eras of Western civilization.